O direito à educação nos tempos pandêmicos no município de Uberlândia: sobre o dito e o feito - Tristão, Vinicius Garcia de Souza (2023)
This research is a master's thesis of the Graduate Program in Education at the Faculty of Education at the Federal University of Uberlândia de Minas Gerais (PPGED/UFU), under the guidance of Prof. Dr. Lucia de Fátima Valente , in the research line of “State, Policies and Management of Education”, whose central theme is “Right to Education and Educational Policies”. In addition, it has the financial support of the Coordination for the Improvement of Higher Education Personnel (CAPES), the agency to which it provided the scholarship during the master's degree so that I could dedicate myself to research. This is a critical research, of bibliographical and documentary origin, of a quantitative and qualitative nature. This dissertation is divided into four sections, the first covering the introduction with the relationships of the researcher's approaches and the theme the right to education, as well as the justifications, objectives and methodological path. The second section brings to light the theoretical framework elements of the right to education (compulsory, subjective, duty of the State and the family). The third section discussed the pandemic in its national context, listing the impacts and actions on education; the fourth section analyzed data from the PNAD and other surveys, that is, to identify in the legal documents (laws, guidelines, decrees, regulations, resolutions, among others) the elements that evidence the guarantee or not of the right to education in the conditions of access and permanence of students in schools in Uberlândia-MG during the period of suspension of face-to-face classes, as well as using data from the city of Uberlândia regarding the number of schools and students served in the Municipal Education Network of Uberlândia, number of students who were reclassified for not complying the school workload with performing PETs, seeking to answer the question that motivated this research and put an end to the final considerations.Important data from surveys such as PNAD, School Census, SIS, data from Uberlândia municipal schools are the references to answer the question: what were the political-pedagogical strategies used officially by face-to-face teaching networks during the covid-19 pandemic? What were the social implications of these policies with regard to guaranteeing the right to education (access and permanence) of children in regular education through the use of remote teaching technologies? In addition to research, important authors are the theoretical framework for the right to education: Chauí (2021); Duarte (2007), Horta (1998), Cury (2010); Oliveira (2002), Araújo (2010). Cury (2010) and Monteiro (2003); for neoliberalism Peroni and Rossi (2019), Veiga e Silva (2017), Dourado, Oliveira and Santos (2007), Carreira and Pinto (2007) COLEMARX (2020); to contextualize the pandemic and remote teaching Arruda (2020), Vieira e Araújo (2021); Moraes and Barros (2007); Petters, (2003); Bastos, Cardoso and Sabbatini (2000); Holmberg (1981); Lacy (1997); Hermida and Bonfim (2006); Pretto, Bonilla and Sena (2020). The results reflect that the pandemic accentuated the differences between public and private education, children were left out of the strategies adopted for remote teaching, considering that they did not have access to the computer, internet, among other important electronic tools in the period of suspension of the classes in the pandemic.